Operando X-ray scattering study of thermoelectric β-Zn4Sb3 - Lasse Rabøl Jørgensen; Christian Moeslund Zeuthen; Kasper Andersen Borup; Martin Roelsgaard; Nils Lau Nyborg Broge; Jonas Beyer; Bo Brummerstedt Iversen (IUCrJ, 2020)
The application of thermoelectrics for energy harvesting depends strongly on operational reliability and it is therefore desirable to investigate the structural integrity of materials under operating conditions. We have developed an operando setup capable of simultaneously measuring X-ray scattering data and electrical resistance on pellets subjected to electrical current. Here, operando investigations of β-Zn4Sb3 are reported at current densities of 0.5, 1.14 and 2.3 A mm−2. At 0.5 A mm−2 no sample decomposition is observed, but Rietveld refinements reveal increased zinc occupancy from the anode to the cathode demonstrating zinc migration under applied current. At 1.14 A mm−2 β-Zn4Sb3 decomposes into ZnSb, but pair distribution function analysis shows that Zn2Sb2 units are preserved during the decomposition. This identifies the mobile zinc in β-Zn4Sb3 as the linkers between the Zn2Sb2 units. At 2.3 A mm−2 severe Joule heating triggers transition into the γ-Zn4Sb3 phase, which eventually decomposes into ZnSb, demonstrating Zn ion mobility also in γ-Zn4Sb3 under electrical current.